Adolescent Kienböck's Disease: A Comparison between Lunate Offloading and Revascularization Procedures - Gillis, Joshua A.; Khouri, Joseph S.; Moran, Steven L. (Journal of Wrist Surgery, 2020)
Objective To evaluate the outcomes and complication rate of surgical management in adolescent patients with Kienböck's disease and compare lunate offloading and revascularization procedures.Methods We performed a retrospective chart review to evaluate adolescent patients with Kienböck's disease between 1990 and 2016 who were surgically managed. Charts were reviewed for demographic information, presence of trauma, range of motion, grip strength, and radiographic parameters pre- and postoperative.Results We assessed 21 wrists in 20 patients. All had failed conservative management and required surgery. Seven patients underwent lunate offloading procedures, most commonly radial-shortening osteotomy, whereas 13 patients had an attempt at revascularization. All patients had either minimal or no pain at a clinical mean clinical follow-up of 63.4 months. Postoperatively, grip strength and radial deviation improved, with no difference between the two groups. Those that underwent joint offloading procedures had less ulnar variance. Eight of 11 patients with a postoperative MRI (magnetic resonance imaging) had evidence of lunate revascularization after a revascularization procedure.Conclusion Surgical management of Kienböck's disease in adolescent patients can yield satisfactory outcomes in those that fail conservative management.Level of Evidence/Type of study This is a Level IV, therapeutic study.
Keywords: Kienböck's disease; adolescent Kienböck's disease; joint offloading; revascularization; bone graft